Chlorophyllin Modulates Gut Microbiota and Inhibits Intestinal Inflammation to Ameliorate Hepatic Fibrosis in Mice - Zheng, Han; You, Yang; Hua, Meiyun; Wu, Pengfei; Liu, Yu; Chen, Zishuo; Zhang, Li; Wei, Haoche; Li, Yan; Luo, Mei; Zeng, Yilan; Liu, Yong; et al. (Frontiers in Physiology, 2018)
Liver fibrosis is an abnormal wound healing response and a common consequence of chronic liver diseases from infection or alcohol/xenobiotic exposure. At the cellular level, liver fibrosis is mediated by trans-differentiation of hepatic stellate cells, which is driven by persistent hepatic and systemic inflammation. However, impaired enterohepatic circulation and gut dysbiosis may indirectly contribute to the biogenesis of liver fibrosis. The composition of the gut microbiota depends on diet composition and host factors. In this study, we examined chlorophyllin, derived from chlorophyll, on the gut microbiota, the intestinal mucosal barrier and liver fibrosis. BALB/c mice received carbon tetrachloride through intraperitoneal injection to induce liver fibrosis and chlorophyllin was administrated via the drinking water. The effects of chlorophyllin on liver fibrosis were evaluated via (1) survival rate, (2) hepatic morphologic analysis, (3) inflammatory factors in both the small intestine and liver, and (4) gut microbiota. Our results indicate that oral administration of chlorophyllin alleviated intestinal and hepatic inflammation and ameliorated liver fibrosis associated with the restoration of the intestinal mucosal barrier. Importantly, oral administration of chlorophyllin promptly transformed the gut microbiota showing down-regulation of the phylum Firmicutes and up-regulation of the phylum Bacteroidetes. In vitro experiments in intestinal epithelial cells showed that chlorophyllin exposure inhibited the NF-κB pathway via IKK-phosphorylation suppression. In conclusion, this study demonstrated the potential application of chlorophyllin for regulating the intestinal microbiota and epithelial cells; and prevent hepatic fibrosis responses to liver injury.